The variability of body composition characteristics in pre- and postmenopausal women from Slovakia - Danková, Zuzana; Siváková, Daniela; Luptáková, Lenka; Cvíčelová, Marta; Čerňanová, Veronika (Anthropological Review, 2014)
Various changes in body composition and body fat distribution are accompaniments of biological ageing, presented mostly in the middle age and significantly notable during the menopause transition. This study aimed to examine the effect of menopausal status on body composition characteristics in 368 apparently healthy women aged 38–61 years. Bioelectrical parameters were measured with a bioimpedance monofrequency analyser (BIA 101) and bioelectric impedance vector analysis (BIVA) was used to analyse tissue electric properties. Data dealing with menopausal status and symptoms as well as life style variables were obtained by the Menopause specific questionnaire. Statistical analysis adjusted for age did not show differences either in the body composition characteristics or in the nutrition and obesity indices between pre– and post–menopausal women. Regression analyses pointed on statistically significant effect (p<0.05) of physical exercise on Xc (B=2.353), FM % (B=–1.746) and MM % (B=1.201), of hypertension on R (B=–22.381), FM % (B=4.468), MM % (B=–2.306), of smoking on Xc (B=1.835), FM % (B=–1.227), MM % (B=0.767), of muscle and joint ache on the FM % (B=1.923) and on MM % (B=–1.061). The age had impact on Xc (B=–13.468) and on the phase angle (B=–1.320). To conclude, in our study group of pre- and postmenopausal Slovak women, age, health and life style factors seem to have more important effect on the body composition characteristics than menopausal status alone.